The 2020 Vision for Food, Agriculture and the Environment in Sub-Saharan Africa: a synthesis - Badiane, Ousmane; Delgado, Christopher L. (International Food Policy Research Institute, 1995)
As part of its 2020 Vision for Food, Agriculture, and the Environment initiative, IFPRI held workshops in three developing regions of the world. The workshop on Sub-Saharan Africa (hereinafter "Africa," for convenience), jointly sponsored by the Office of the Coordinator-General of the Conference of Ministers of Agriculture of West and Central Africa and IFPRI, was held in Saly Portudal, Senegal, December 14-17, 1994. This synthesis is based on intensive discussion among two dozen African researchers, technical experts, and policymakers who participated in the workshop. A deliberate attempt was made to break the mold of outsiders conceptualizing Africa's issues. A drafting committee of eight Africans from all parts of the region brought together Anglophones and Francophones from both policymaking and research backgrounds. Where useful, statistics and elaborations to flesh out points made by the drafting committee were added later by IFPRI staff, but the tenor of the workshop statement has been maintained. This strategy will be helpful to the 2020 Vision initiative in defining forward-looking priorities for action in Africa.